Colonic non-polypoid (serrated) lesions Nicht polypoide (serratierte) läsionen des kolon - Vieth, M.; Lambert, R. (Verdauungskrankheiten, 2010)
Recently, the emerging role of non-polypoid precursors of colorectal cancer has challenged the conventional polyp-cancer sequence. The impact of colonoscopy in cancer prevention depends on its reliability in the diagnosis of colorectal neoplasia when the lesion does not extend beyond the submucosa and is potentially curable. Apragmatic classification of superficial neoplastic lesions that takes into account these changes, is based on a two-step strategy of: (a) endoscopic diagnosis with an initial detection and characterization, followed by, (b) treatment implementation, such as lesion resection or ablation. The estimation of the risk of progression is based on the prediction of histology from the morphological appearance of the lesion and includes: (a) distinction between neoplastic and non-neoplastic lesions; (b) identification of different categories of non-serrated and serrated lesions; and (c) determination of the localization in the proximal or distal colon, which has an impact on the morphology and behavior of the lesion. © 2010 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Adenoma; Carcinoma; Colon; Serrated